2004
DOI: 10.1177/0146167204264333
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Need for Closure on Conservative Beliefs and Racism: Differential Mediation by Authoritarian Submission and Authoritarian Dominance

Abstract: The present study explores the influence of need for closure as well as authoritarian submission (Right-Wing Authoritarianism [RWA]) and authoritarian dominance (Social Dominance Orientation [SDO]) on the genesis of conservative beliefs and racism. For this purpose, two structural equation models were compared. In Model 1, RWA and SDO were entered as independent variables and the need for closure facets Decisiveness and Need for Simple Structure acted as mediator variables. In Model 2, the need for closure fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
257
1
19

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 282 publications
(307 citation statements)
references
References 63 publications
30
257
1
19
Order By: Relevance
“…Past work has shown correlationally that PNS produces prejudice and discrimination via mediation through SDO and RWA (e.g., Altemeyer, 1998;Heaven & Bucci, 2001;Van Hiel, Pandelaere, & Duriez, 2004). The current work bolsters these findings by providing experimental evidence that motivational needs for structure may contribute, in part, to the attractiveness of hierarchy.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Past work has shown correlationally that PNS produces prejudice and discrimination via mediation through SDO and RWA (e.g., Altemeyer, 1998;Heaven & Bucci, 2001;Van Hiel, Pandelaere, & Duriez, 2004). The current work bolsters these findings by providing experimental evidence that motivational needs for structure may contribute, in part, to the attractiveness of hierarchy.…”
Section: Discussionsupporting
confidence: 63%
“…Someone whose sense of personal control has been threatened thus might find hierarchy appealing as a means of reestablishing a more general sense of structure. Indeed, past theoretical work has proposed the possibility that hierarchies fulfill psychological needs for structure (Magee & Galinsky, 2008), and correlational evidence suggests that needs for structure and hierarchy-enhancing ideology are related (Jost, Glaser, Kruglanski, & Sulloway, 2003;Van Hiel, Pandelaere, & Duriez, 2004).…”
Section: Compensatory Control and The Endorsement Of Hierarchymentioning
confidence: 99%
“…However, studies in the domain of social cognition have provided empirical evidence for the basic role of individual differences in motivated cognition, and particularly NFC, in the development and perseverance of personal values, beliefs, and social attitudes (e.g., Calogero, Bardi, & Sutton, 2009;Van Hiel et al, 2004). Socialization theories did not consider the possibility that parents and children may also resemble each other in their general cognitive style giving rise to ideological and intergroup attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, NFC shows a remarkable conceptual fit with the motivated cognitive style characteristics which Allport (1954) described as "the prejudiced personality" and several studies have indeed demonstrated that NFC is strongly related to various forms of prejudice, including gender-based, racial, and anti-immigrant prejudice (e.g., Cunningham, Nezlek, & Banaji, 2004;Roets, Van Hiel, & Dhont, 2012;Van Hiel, Pandelaere, & Duriez, 2004). In addition, scholars have also demonstrated that the effects of NFC on anti-immigrant prejudice are mediated by the endorsement of authoritarian views (e.g., Van Hiel et al, 2004).…”
mentioning
confidence: 98%
See 1 more Smart Citation